Transmembrane tumor necrosis factor-alpha sensitizes adipocytes to insulin. (5th May 2015) - Zhou, Wenjing; Yang, Peng; Liu, Li; Zheng, Shan; Zeng, Qingling; Liang, Huifang; Zhu, Yazhen; Zhang, Zunyue; Wang, Jing; Yin, Bingjiao; Gong, Feili; Wu, Yiping; et al.
Highlights: tmTNF-α sensitizes adipocytes to insulin via promoting insulin signaling. tmTNF-α downregulates proinflammatory adipokine secretion via inactivation of NF-κB. tmTNF-α increases adiponectin expression and insulin sensitivity via PPAR-γ pathway. tmTNF-α sensitizes adipocytes to insulin via forward signaling. Graphical Abstract: Abstract: Transmembrane TNF-α (tmTNF-α) acts both as a ligand, delivering 'forward signaling' via TNFR, and as a receptor, transducing 'reverse signaling'. The contradiction of available data regarding the effect of tmTNF-α on insulin resistance may be due to imbalance in both signals. Here, we demonstrated that high glucose-induced impairment of insulin-stimulated glucose uptake by 3T3-L1 adipocytes was concomitant with decreased tmTNF-α expression and increased soluble TNF-α (sTNF-α) secretion. However, when TACE was inhibited, preventing the conversion of tmTNF-α to sTNF-α, this insulin resistance was partially reversed, indicating a salutary role of tmTNF-α. Treatment of 3T3-L1 adipocytes with exogenous tmTNF-α promoted insulin-induced phosphorylation of IRS-1 and Akt, facilitated GLUT4 expression and membrane translocation, and increased glucose uptake while addition of sTNF-α resulted in the opposite effect. Furthermore, tmTNF-α downregulated the production of IL-6 and MCP-1 via NF-κB inactivation, as silencing of A20, an inhibitor for NF-κB, by siRNA, abolished this effect of tmTNF-α. However, tmTNF-α upregulated adiponectin expression through the PPAR-γ pathway, as inhibition of PPAR-γ by GW9662 abrogated both tmTNF-α-induced adiponectin transcription and glucose uptake. Our data suggest that tmTNF-α functions as an insulin sensitizer via forward signaling.